Lactate metabolism in potato tubers deficient in lactate dehydrogenase activity - Sweetlove, L; Dunford, R; Ratcliffe, R; Kruger, N (2000)
The aim of this work was to investigate the effect of decreased activity of lactate dehydrogenase (EC 1.1.1.27; LDH) on lactate metabolism in potato tubers. By expressing a cDNA-encoding potato tuber LDH in the antisense orientation, we generated transgenic potato plants with a preferential decrease in two of the five isozymes of LDH. Surprisingly, transgenic tubers grown under normoxic conditions did not contain less lactate, but rather instead contained approximately two-fold more lactate than control tubers. This result is explicable if the decreased isozymes of LDH are responsible for the oxidation of lactate to pyrurate in viva. This was confirmed by measurements of the rate of metabolism of lactate supplied to tuber discs: the rate in transgenic tubers was approximately half that of control tubers. The decrease in LDH activity had no measurable effect on the accumulation of lactate in cold-stored tubers under anoxia, nor during the subsequent utilization of rids lactate upon return to normosia. In both control and transgenic tubers, the accumulation of lactate during anoxia was not accompanied by an induction of LDH activity or a change in isozyme distribution. In contrast, the metabolism of lactate after a period of anoxia was accompanied by a two-fold increase in LDH activity and the induction of two isozymes that were distinct from those which had been decreased in the transgenic plants.